2010
DOI: 10.33275/1727-7485.9.2010.397
|View full text |Cite
|
Sign up to set email alerts
|

KamLAND-experiment and soliton-like nuclear georeactor

Abstract: We give an alternative description of the new data produced in the KamLAND experiment, assuming the existence of a natural nuclear reactor on the boundary of the liquid and solid phases of the Earth's core. Analyzing the uncertainty of antineutrino spectrum of georeactor origin, we show that the theoretical (which takes into account the soliton-like nuclear georeactor with power about 20 TW) reactor antineutrino spectrum describes with good accuracy the new experimental KamLAND-data. 2-5 2 2 At the same time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It's strange, but it is true and it is confirmed by inverse correlation between the solar magnetic field (Figure 1) and the nuclear georeactor thermal power over the period 2002-2009 (Figure 7b). Thus, on the one hand, such a coordinated behavior of the solar magnetic field and the nuclear georeactor thermal power is an indirect confirmation of reality of the "axion mechanism-nuclear georeactor" energy chain and, on the other hand, according to the estimated power of various geophysical processes [29], such a generalized mechanism can provide the solarterrestrial correlations shown in Figure 1 effectively.…”
Section: Soliton-like Nuclear Georeactor and Axion Mechanism Of The E...mentioning
confidence: 78%
See 4 more Smart Citations
“…It's strange, but it is true and it is confirmed by inverse correlation between the solar magnetic field (Figure 1) and the nuclear georeactor thermal power over the period 2002-2009 (Figure 7b). Thus, on the one hand, such a coordinated behavior of the solar magnetic field and the nuclear georeactor thermal power is an indirect confirmation of reality of the "axion mechanism-nuclear georeactor" energy chain and, on the other hand, according to the estimated power of various geophysical processes [29], such a generalized mechanism can provide the solarterrestrial correlations shown in Figure 1 effectively.…”
Section: Soliton-like Nuclear Georeactor and Axion Mechanism Of The E...mentioning
confidence: 78%
“…We have to note that, in spite of the fact that the experimental KamLAND-data are well described within the framework of georeactor model [16,17] (see Figure 5) and the location of soliton-like nuclear georeactors (Figure 6 [17]) is determined by triangulation of the Kam-LAND [18] and Borexino data [19], some geophysicists have doubts not only about existence of the georeactor, but in the first place about its power. In this connection we would like to pay attention to the strange restriction (W ≤ 6.2 TW) on the value of georeactor thermal power W, which, unfortunately, has been frequently met in the scientific literature recently [19][20][21][22].…”
Section: Soliton-like Nuclear Georeactor and Axion Mechanism Of The E...mentioning
confidence: 97%
See 3 more Smart Citations